Pregabalin Misuse and Abuse in Jordan (International Journal of Scientific Research and Management (IJSRM), 2018)
Pregabalin are widely used in neurology, psychiatry and primary healthcare for a range of clinical conditions but are increasingly being reported as possessing a potential for misuse. In fact, increasing levels of both prescriptions and related fatalities, together with an anecdotally growing black market, have been reported in Jordan.